Effets mésoéconomiques de la crise de la covid-19 - Jérémie Bastien (Revue de la Régulation)
This article provides conceptual framework to determine the impact of macroeconomic shocks on European professional football. It identifies the channels by which the effects of the Covid-19 pandemic crisis were transmitted to this specific meso-system. In the short term, the crisis resulted in a decrease of income for clubs, counterbalanced by support measures of sport organizations and governments, such as state-guaranteed loans leading to an increase of clubs’debt. We also chart long term scenarios of the economic recovery likely to minimize some consequences of the crisis on professional football clubs. Concerning their capacity to sell sport events to TV broadcasters and visibility space to sponsors, the clubs will not be much affected by the crisis. By sustaining the price level of players, however, the increase of clubs’debt and the reinforcement of their dependence on TV broadcasters intensify the endogenous contradictions resulting from the financialization of European professional football. The covid-19 crisis thus only accelerates and amplifies the structural risk in this meso-system.